IWB Influenced By Digital Leadership, With A Climate For Initiative And Job Autonomy As Mediators - Ramayana Simarmata; Elok Savitri Pusparini (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
Company management is expected to be able to carry out new strategies innovatively, this is of course closely related to digital leadership which can influence the climate in the environment and work autonomy. This research aims to see the impact of digital leadership on innovative work behavior with a fork in the mediating role of climate for initiative and work autonomy. This research uses a population, namely employees at Public Institutions at the Head Office, Jakarta using a sample of 262 respondents. Data hypothesis testing in this research was carried out through structural equation model (SEM) analysis using the LIS application. The research results show that digital leadership has a positive and significant effect on innovative work behavior. Digital leadership has a positive and significant effect on the initiative climate. Initiative climate has a positive and significant effect on innovative work behavior. Digital leadership has a positive and significant effect on work autonomy. Work autonomy has a positive and significant effect on innovative work behavior. Climate for Initiative can mediate the relationship between digital leadership and innovative work behavior. Work autonomy can mediate the relationship between digital leadership and innovative work behavior.